Pembuatan Dan Evaluasi Pati Talas (Colocasia esculenta Schoot) Termodifikasi dengan Bakteri Asam Laktat (Lactobacillus sp) - Wira Noviana Suhery; Deni Anggraini; Novtafia Endri (Jurnal Sains Farmasi & Klinis, 2015)
Production and evaluation of modified taro (Colocasia esculenta Schott) starch by lactic acid bacteria (Lactobacillus sp) has been done. The purpose of this study was to observe the effect of lactic acid bacteria to the yield of taro starch and to evaluate physicochemical of starch. The evaluation which includes organoleptic, moisture content, pH, angle of repose, swelling power, gelatination temperature, amylose content, and examination of the surface shape of starch granules using SEM (Scanning Electron Microscope). The result showed that modified taro starch yield higher (19,12%) than native taro starch (11,79%). Modified taro starch of organoleptic examination showed better results where the smell was slighly reduced and the colour was white. Meanwhile, from the results of the evaluation of swelling power, gelatination temperature, and amylose content showed an increase. In addition, the modified taro starch granule were rougher due to some holes presented distinctively.